Effective food systems innovations: An inventory of evidence from Bangladesh, Ethiopia, Nigeria, Viet Nam, and other low-and middle-income countries - Lecoutere, Els; Van den Berg, Marrit; de Brauw, Alan (International Food Policy Research Institute, 2021)
To address malnutrition in low- and middle income countries (LMICs), more evidence is needed about the potential of food system innovations to help guide the transformation towards healthier, more sustainable, and equitable food systems. This paper reviews the literature on food system innovations in the food environment and addressing consumer behavior on diet and nutrition-related outcomes in Bangladesh, Ethiopia, Nigeria, Viet Nam, and other LMICs, then highlights promising innovations and demonstrates gaps in the literature. In the food environment, promising innovations include nutrition-relevant multi-sectoral national backed by effective implementation; institutional purchasing offering healthy meals in school or factory environments; compulsory nutrition labelling; and fortified foods, if these can be durably offered or viably commercialised. Promising innovations influencing consumer behavior include unhealthy food taxes; large-scale information campaigns raising awareness about specific unhealthy food items; and campaigns that provide information and/or fortified food (supplements) to address nutrition of infants and young children. Promoting women’s empowerment and targeting women with nutrition information could be effective food system innovations addressing consumer behavior, but deliberation is needed about risks of emphasizing the instrumental role of gender equity and women’s empowerment for nutrition or reinforcing gender roles and increasing women’s responsibilities. That said, our review also demonstrates a general lack of evidence on most types of food system innovations in the four primary countries of study. More evidence is needed on several types of food systems innovations before definitive advice can be given on guiding food systems transformations towards healthier diet outcomes. This review therefore acts as a starting point for addressing country-specific food system challenges and identifies needs for further research.